2012
DOI: 10.29309/tpmj/2012.19.02.2011
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection;

Abstract: Objective: To determine the frequency of H. pylori infection in dyspeptic patients undergoing endoscopy at a tertiary care centerin Karachi. Data source: Patients undergoing endoscopy at Liaquat National Hospital, Karachi. Design of study: Cross sectional descriptivestudy. Setting: Department of Gastroenterology, Liaquat National Hospital, Karachi. Period: May 2008–October 2008. Material andmethods: All adult patients with symptoms of dyspepsia for more than 1 month duration were included. Patients with upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Also the results of adult are consistent with the study conducted by 50 whom they found that the prevalence of H.pylori in age group 15 -25 The prevalence of H.pyloriinfection increased with age, but a slight decrease in prevalence in the oldest age group, is probably due to decreasing specific immune response among older individuals and /or to decreased number of microorganisms as a result of gastric atrophy 18,37 .…”
Section: Discussionsupporting
confidence: 88%
“…Also the results of adult are consistent with the study conducted by 50 whom they found that the prevalence of H.pylori in age group 15 -25 The prevalence of H.pyloriinfection increased with age, but a slight decrease in prevalence in the oldest age group, is probably due to decreasing specific immune response among older individuals and /or to decreased number of microorganisms as a result of gastric atrophy 18,37 .…”
Section: Discussionsupporting
confidence: 88%
“…It is estimated that the prevalence of H. pylori infection among adults in Pakistan is around 80-85%. However, there is a dearth of research on this topic in the Pakistani population [3].…”
Section: Introductionmentioning
confidence: 99%